Humidified rapid‐insufflation ventilatory exchange is a means of oxygenation during rigid bronchoscopy: A case series. Issue 2 (25th January 2022) - Kornafeld, Anna; Fernandez‐Bussy, Sebastian; Abia‐Trujillo, David; Garcia, Juan C.; Chadha, Ryan M.
Abstract: Humidified rapid‐insufflation ventilatory exchange (HRIVE) is an option for maintenance of oxygenation. This technique allows for oxygenation while the patient is apnoeic due to continuous positive airway pressure and gas exchange through flow‐dependent dead space flushing. There is no study about the usage of HRIVE during rigid bronchoscopy. This retrospective study looked at rigid bronchoscopy cases utilizing HRIVE. Data points assessing adequacy of oxygenation and ventilation were recorded at time points: oxygen saturation (SpO2 ), partial pressure of oxygen (PaO2 ) and partial pressure of carbon dioxide (PaCO2 ). Our nine cases had an average baseline SpO2 of 99.26%, 95.56% at 10 min into HRIVE and 95.27% at the end of HRIVE. The average baseline PaO2 was 309.01 mmHg, 124.99 mmHg at 10 min into HRIVE and 128.17 mmHg at the end of HRIVE. The average baseline PaCO2 was 43.26 mmHg, 68.76 mmHg at 10 min into HRIVE and 75.52 mmHg at the end of HRIVE. The average pre‐HRIVE end‐tidal CO2 (ETCO2 ) was 38.56 mmHg and the average post‐HRIVE ETCO2 was 61.22 mmHg. The average baseline pH was 7.36, 7.22 at 10 min into HRIVE and 7.19 at the end of HRIVE. In this small cohort study, HRIVE was able to maintain adequate oxygenation via the rigid bronchoscope in a select group of patients. Hypercapnia and respiratory acidosis did result after 10 min, which may predispose certain patient populations to complications. HRIVE potentially offers an additional option of oxygenation via the rigid bronchoscope. Abstract : Humidified rapid‐insufflation ventilatory exchange (HRIVE) was able to maintain adequate oxygenation via the rigid bronchoscope in a select group of patients. We suggest HRIVE now potentially offers an option of oxygenation via the rigid bronchoscope that allows for continuous oxygenation without interruption of the procedure, a cost‐effective option compared to high‐frequency jet ventilation, and a less labour‐intensive option compared to low‐frequency jet ventilation.